Understanding Transparency Perception in Architecture: Presentation of the Simplified Perforated Model. (January 2013) - Brzezicki, Marcin
Issues of transparency perception are addressed from an architectural perspective, pointing out previously neglected factors that greatly influence this phenomenon in the scale of a building. The simplified perforated model of a transparent surface presented in the paper has been based on previously developed theories and involves the balance of light reflected versus light transmitted. Its aim is to facilitate an understanding of non-intuitive phenomena related to transparency (eg dynamically changing reflectance) for readers without advanced knowledge of molecular physics. A verification of the presented model has been based on the comparison of optical performance of the model with the results of Fresnel's equations for light-transmitting materials. The presented methodology is intended to be used both in the design and explanatory stages of architectural practice and vision research. Incorporation of architectural issues could enrich the perspective of scientists representing other disciplines.